Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.